Technical and Economic Potential of Concentrating Solar Thermal Power Generation in India - Purohit, Ishan (Elsevier, 2018)
This study aims to assess the technical and economic potential of concentrating solar power (CSP) generation in India. The potential of CSP systems is estimated on the basis of a detailed solar radiation and land resource assessment in 591 districts across the country. The land suitability, favorable solar resource conditions and wind power density over the vicinity have been considered key parameters for potential estimation. On the basis of a district-wise solar and land resource assessment, the technical potential of CSP systems is estimated over 1500 GW at an annual direct normal irradiance (DNI) over 1800 kWh/m2 and wind power density (WPD) ≥150 W/m2 after taking into accounts the viability of different CSP technologies and land suitability criteria. The economic potential of CSP is estimated at 571 GW at an annual DNI over 2000 kWh/m2 and WPD≥150 W/m2 in India. The technical evaluation of CSP technologies over the potential locations have been carried through System Advisor Model (SAM) Software using the Typical Meteorological Year data of Meteonorm 7.0 weather database. In near future, it is anticipated that locations with DNI values ≥1600–1800 kWh/m2 could also become economically feasible with the development of new technologies, advancement of materials, efficient and cost-effective thermal energy storage, economy of scale, manufacturing capability along with the enhanced policy measures, etc. In the long-term, it is possible to exploit over 2700 GW solar power through CSP in India with an annual DNI ≥1600 kWh/m2 and WPD≥150 W/m2. The findings of this study can be used for identification of niche areas for CSP projects in India.